Understanding the conformational changes and molecular structure of furoyl thioureas upon substitution - Ramos Cairo, Raúl (2017)
1-Acyl thioureas [R1C(O)NHC(S)NR2R3] are shown to display conformational flexibility depending on the degree of substitution at the nitrogen atom. The conformational landscape and structural features for two closely related thioureas having R1 = 2-furoyl have been studied. The un-substituted 2-furoyl thiourea (I) and its dimethyl analogue, i.e. 1-(2-furoyl)-3,3-dimethyl thiourea (II), have been synthesized and fully characterized by spectroscopic (FT-IR, 1H and 13C NMR) and elemental analysis. According to single crystal X-ray diffraction analysis, compounds I and II crystallize in the monoclinic space group P21/c. In the compound I, the trans–cis geometry of the almost planar thiourea unit is stabilized by intramolecular Nsingle bondH ⋯ Odouble bondC hydrogen bond between the H atom of the cis thioamide and the carbonyl O atom. In compound II, however, the acyl thiourea group is non-planar, in good agreement with the potential energy curve computed at the B3LYP/6-31 + G(d,p) level of approximation. Centrosymmetric dimers generated by intermolecular N — H ⋯ O = C hydrogen bond forming R22(8) motif are present in the crystals. Intermolecular interactions have been rationalized in terms of topological partitions of the electron distributions and Hirshfeld surface analysis, which showed the occurrence of S ⋯ H, O ⋯ H and H ⋯ H contacts that display an important role to crystal packing stabilization of both thiourea derivatives.